The Effect Of Competence And Incentives Towards Teaching Quality At Paud Pelita Hati Dusun Pulau Jelmu Kecamatan Jujuhan Kabupaten Bungo Provinsi Jambi - Fitriani, Fitriani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This research is attracted by the important role of the teacher which cannot be ignored, both the government, stakeholders and the teacher himself. Teachers must always improve their competence in carrying out their duties, teachers must master the main areas of work, so that teachers become professional teachers. The results of the 2015 Teacher Competency Test (UKG) were still low, the average teacher score reached 48.69 in Provinsi Jambi. The researcher found data on teachers who still had high school qualifications teaching as PAUD teachers, although there were those with bachelor's degrees, but that was very small and they were reluctant teaching in PAUD due to the lack of incentives received by PAUD teachers ranging from Rp. 300-600 only per month. This study aims to determine the effect of competence and incentives on the quality of teaching teachers at PAUD Pelita Hati, Pulau Jelmu Kecamatan Jujuhan, Kabupaten Bungo, Provinsi Jambi. The research method is a quantitative descriptive method and the approach used is a quantitative approach. The population and sample were all Pelita Hati PAUD teachers, totaling 8 people. The results of this study found that there was a significant effect of teacher competence and incentives on teacher teaching quality because it had an Fcount of 3.671 > Ftable of 3.24 and a sig. 0.035 < 0.05. The results of this study show that competence and incentives can jointly support the improvement of teacher teaching quality. The competence possessed by the teacher and supported by the incentives provided by the school to the teacher contributes to the high quality of teaching the teacher, both coming from each individual and the motivation given by the school principal will automatically make the teacher passionate about carrying out his duties